Three new species of the genus Cloeodes Traver (Ephemeroptera: Baetidae) from Uruguay - Nieto Peñalver, María Carolina (2011)
The genus Cloeodes is poorly reported for Uruguay, until now only C. aymara was described from this region. Here we describe three new species of Cloeodes from this country: C. dialutoi, C. guenoa and C. vaimaca, all of them based on nymphs. The species C. opacus is reported for the first time in Uruguay. A discussion of each taxon is included as well as drawings of the new species. A revised and updated key for male imagos and nymphs of South American species of Cloeodes is presented.